Correction to: The Edinburgh Consensus: preparing for the advent of disease-modifying therapies for Alzheimer’s disease - Craig W. Ritchie; Tom C. Russ; Sube Banerjee; Bob Barber; Andrew Boaden; Nick C. Fox; Clive Holmes; Jeremy D. Isaacs; Ira Leroi; Simon Lovestone; Matt Norton; John O’Brien; et al. (Alzheimer’s Research & Therapy, 2018)
Since the publication of this article [1], it has come to the attention of the authors that information for one of the authors was not included in the competing interests section. Craig Richie has declared potential competing interests with the following companies; Janssen, Eisai, Pfizer, Eli Lilly, Roche Diagnostics, Boeringher Ingleheim, Novartis, AC Immune, Ixico, Aridhia, Amgen, Berry Consultants, Lundbeck, Sanofi, Quintiles (IQVIA) and Takeda. The full competing interests section for this article can be found below.